Modifications in activation of lower limb muscles as a function of initial foot position in cycling - Padulo, J.; Powell, D. W.; Ardigo, L. P.; Viggiano, D. (Journal of Electromyography and Kinesiology, 2015)
Cyclic movements, such as walking/cycling, require the activity of spinal-circuits, the central-pattern-generators (CPG). To our knowledge little work has been done to investigate the activation of these circuits, e.g., the muscular and kinematic activity during cycling initiation. This study aims to detail the muscle output properties as a function of the initial lower limb-position using a simple cycling paradigm. Therefore, subjects were required to pedal on a cycle-ergometer in seated position starting at different-crank-angles (0-150°). Surface-electromyography was recorded from the gluteus major (GL), vastus lateralis (VL), and gastrocnemius medialis (GM), while crank position was recorded using a linear-encoder. Gluteus major peak-activity (PA) occurred at 65.0 ± 12.4° when starting with 0° initial crank position (ICP), while occurred maximally at 110.5 ± 2.9 when starting with 70° ICP. Vastus lateralis PA occurred at 40.7 ± 8.8° with 0° ICP, whereas with 70° ICP PA occurred at 103.4 ± 4.0°. Similarly, GM PA occurred at 112.0 ± 10.7° with 0° ICP, whereas with 70° ICP PA occurred at 142.5 ± 4.2° PA. Gluteus major and gastrocnemius medialis showed similar PA phase shifts, which may suggest they are controlled by same local circuitry, in agreement with their common spinal origin, i.e., motoneurons pool in S1-S2.